Overview of modern technologies for residential automation - Polikanov, К. А.; Sotnik, S. V. (ХНУРЕ, 2025)
The work provides an overview of modern technologies for the automation of residential premises. The key directions in the development of smart home systems are considered, including the use of the Internet of Things, energy-saving solutions, climate control, as well as security and video surveillance systems. Examples of popular technologies and manufacturers are given. У роботі наведено огляд сучасних технологій автоматизації житлових приміщень. Розглянуто ключові напрями розвитку систем «розумного будинку», зокрема застосування Інтернету речей, рішень для енергозбереження, клімат-контролю, а також систем безпеки і відеоспостереження. Наведено приклади популярних технологій та виробників.
Огляд сучасних технологій для автоматизації житлових приміщень
Keywords: автоматизація житлових приміщень; automation of residential premises